Activated protein C inhalation: A novel therapeutic strategy for acute lung injury - Bo, Lulong (International Scientific Literature, Inc., 2011)
Acute lung injury (ALI) is a critical illness syndrome with a mortality rate of 25–40%. Despite recent advances of our understanding of the pathophysiology of ALI, no pharmacologic therapies have been proven effective. The key pathogenesis of ALI is the activation of the coagulation cascade and impaired fibrinolysis, resulting in extensive fibrin and hyaline membrane deposition. Activated protein C (APC), an endogenous protein that promotes fibrinolysis and inhibits thrombosis, can modulate the coagulation and inflammation associated with ALI. It is therefore reasonable to suggest that preventing the progression of pulmonary coagulopathy, by restoring normal intraalveolar levels of protein C, will be of therapeutic benefit to patients with ALI. However, a recent clinical trial demonstrated that APC did not improve outcomes from ALI, raising the possibility that the method of APC administration, intravenous infusion or inhalation, may influence the outcomes. In this article we propose the hypothesis that APC inhalation might be a promising and novel choice in the treatment of ALI.